Bacterial Communities and Prediction of Microbial Metabolic Pathway in Rice Wine Koji From Different Regions in China - Zhao, Xinxin; Xiang, Fanshu; Tang, Fengxian; Cai, Wenchao; Guo, Zhuang; Hou, Qiangchuan; Yang, Xinquan; Song, Wen; Shan, Chunhui (Frontiers in Microbiology, 2022)
Rice wine koji is a traditional self-made fermented food in China, which is nutritious and delicious. The final quality of rice wine koji is closely related to its microbial community structure. However, the diversity of natural microorganisms in rice wine koji from different regions has not been evaluated. In this study, the microbial population of 92 naturally fermented rice koji samples collected from Hubei, Guangxi and Sichuan was systematically analyzed by high-throughput sequencing. High-throughput sequencing showed that 22 phylum and 479 bacterial generics were identified in all rice wine koji samples. Weissella, Pediococcus, Lactobacillus, Enterobacter, Lactococcus, Pantoea, Bacillus, Staphylococcus and Leuconostoc are the dominant genera in rice wine koji. The bacterial community structure of rice wine koji samples from different regions is significantly different (p < 0.05). The bacterial community composition of HB and GX samples is similar, but significantly different from SC samples (p < 0.05). These differences may be caused by geographical, environmental or manufacturing differences. In addition, the results of microbial phenotype prediction by BugBase and bacterial functional potential prediction by PICRUSt showed that 8 of the 9 predicted phenotypic functions of rice wine koji samples from different regions were significantly different (p < 0.05), and the bacteria metabolism in rice wine koji samples was vigorous.